Entamoeba gingivalis: epidemiology, genetic diversity and association with oral microbiota signatures in North Eastern Tanzania. Issue 1 (1st January 2021) - Stensvold, Christen Rune; Nielsen, Michelle; Baraka, Vito; Lood, Rolf; Fuursted, Kurt; Nielsen, Henrik Vedel
ABSTRACT: Background: Entamoeba gingivalis has been associated with periodontal diseases. Baseline data from the background population, which could help delimit the role of the parasite in health and disease, remain limited. Objective: To describe epidemiological features, genetic diversity, and associations with oral microbiome signatures of E. gingivalis colonisation in Tanzanians with non-oral/non-dental diseases. Methods: DNAs from 92 oral washings from 52 participants were subject to metabarcoding of ribosomal genes. DNA sequences were identified to genus level and submitted to oral microbiota diversity analyses. Results: Sixteen (31%) of the 52 study participants were E. gingivalis- positive, with no difference in positivity rate according to gender or age. Only one subtype (ST1) was found. Individuals testing positive for E. gingivalis had higher oral microbiota alpha diversity than those testing negative ( P = 0.03). Eight of the top-ten most common bacterial genera were shared between the two groups ( Alloprevotella, Fusobacterium, Gemella, Haemophilus, Neisseria, Porphyromonas, Prevotella, Streptococcus, and Veillonella) . Meanwhile, E. gingivalis carriers and non-carriers were more likely to have Aggregatibacter and Rothia, respectively, among the top-ten most common genera. Conclusion: About one third of the cohort carried E. gingivalis ST1, and carriers had higher oral microbiome diversity and were more predominantly colonized by Aggregatibacter .